Reinterpretasi Konsepsi Ki Hadjar Dewantara: Studi Kritis dalam Perspektif Filosofis-Pedagogis - Gantina Gantina; Yusuf Tri Herlambang; Tatang Muhtar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Education plays an important role in human life as the main foundation in developing the quality of individual. Ki Hajar Dewantara's view gave rise to a comprehensive and integrated concept of education covering various aspects, such as intelligence, emotional, physical, aesthetic, social and spiritual aspects. The purpose of this study is to examine and describe Ki Hajar Dewantara's pedagogical ideas in relation to contemporary education. This study uses the Literature Study research method by examining various relevant literature sources. The results of the study state that the concept of education from Dewantara's perspective must be centered on students, emphasize freedom in learning, and be based on local moral and cultural values. In addition, Dewantara emphasizes the importance of character education and individual empowerment in order to achieve their best potential. Based on the results of the study, it can be concluded that Dewantara's view provides a solid philosophical basis for an inclusive, value-oriented, and individual and community welfare education system. This perspective remains relevant in facing the challenges of education in the modern era by balancing academic aspects and character and moral formation. This study provides valuable insights in designing more comprehensive education policies based on humanitarian values.